Social and Economic Determinants of Human Trafficking: A Role of Forced Labour in Punjab, Pakistan - Joiya, Salman Azam; Quddus, Muhammad Abdul (iRASD Journal of Economics, 2022)
This paper analyses the relationship between human trafficking and the socio-demographic and economic variables that impact it. A total of 200 respondents from five regions of Punjab, Pakistan was interviewed, and the responses were recorded on a structured questionnaire. This study has conducted a descriptive and logistic regression analysis to measure the impact of independent variables on the dependent ones. The results show that gender, living area, marital status, family size, and education up to the primary level has a significant impact on human trafficking. All economic determinants used in the analysis show significant results. The income level and outstanding debt have a negative significant impact on human trafficking; whereas, financial stress increases it with significant results. In order to eliminate human trafficking, the study is concluded by recommending the influential and increased role of law enforcement agencies and revitalising the socio-economic and demographic structure of the country by creating economic opportunities.